2013
DOI: 10.1016/j.vetpar.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the pepsin digestion method for anisakids inspection in the fishing industry

Abstract: During the last 50 years human anisakiasis has been rising while parasites have increased their prevalence at determined fisheries becoming an emergent major public health problem. Although artificial enzymatic digestion procedure by CODEX (STAN 244-2004: standard for salted Atlantic herring and salted sprat) is the recommended protocol for anisakids inspection, no international agreement has been achieved in veterinary and scientific digestion protocols to regulate this growing source of biological hazard in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 41 publications
0
39
1
2
Order By: Relevance
“…In the European Union the official method for larvae detection is visual inspection and candling of fish fillets indicated in Regulation EC 2074/2005 but it is known that this methods not detect all the larvae present in the flesh of fish (Levsen et al 2005) or in seafood preparations unlike other more accurate and efficient methods as, in particularly, artificial digestion. Several digestion methods have been proposed in the literature (Jackson et al 1981) and recent studies have shown that pepsin and HCl conentration may be different according to the material to be digested (Llarena-Reino et. al.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Union the official method for larvae detection is visual inspection and candling of fish fillets indicated in Regulation EC 2074/2005 but it is known that this methods not detect all the larvae present in the flesh of fish (Levsen et al 2005) or in seafood preparations unlike other more accurate and efficient methods as, in particularly, artificial digestion. Several digestion methods have been proposed in the literature (Jackson et al 1981) and recent studies have shown that pepsin and HCl conentration may be different according to the material to be digested (Llarena-Reino et. al.…”
Section: Discussionmentioning
confidence: 99%
“…The artificial digestion of the flesh and visceral cavity of shad was carried out on the basis of an optimized artificial digestion protocol (Llarena-Reino et al 2013a). The flesh was digested at 37-40°C during approximately 3-4 h (3 h for visceral cavity material) in an ACM-11806 Magnetic Stirrer Multiplate, using a weight/volume pepsin ratio of 1:20, understanding that ratio as 20 ml of a 0.5 % pepsin solution in HCl 0.063 M (pH 1.5) for 1 g of flesh.…”
Section: Artificial Enzymatic Digestionmentioning
confidence: 99%
“…Anisakiasis can be prevented by freezing fish (at -20°C or below for 7 days, or at -35°C or below for 15 h). At present, detection of Anisakidae nematodes in fishery products is performed by different methods based on visual inspection (candling), light microscopy, UV examination of fish fillets after pressing and freezing, molecular analysis and chlorine-peptic digestion [10]. In the European Union, the official method for larva detection is the direct observation [11], sometimes coupled with the more accurate digestion method [10].…”
Section: Anisakidaementioning
confidence: 99%